Influence of codoping of YAG:Dy for high temperature phosphor thermometry - Hertle, Ellen Elisabeth; Chepyga, Liudmyla; Batentschuk, Miroslaw; Zigan, Lars (Journal of Luminescence, 2017)
The effects of codoping on the temperature-dependent luminescence of YAG:Dy were investigated for application in high temperature thermometry. YAG:Dy is a well-known thermographic phosphor suitable for high temperature measurements. However, its decay time is too long for studying temperatures in fast transient technical processes. Codoping is a known method for increasing the signal intensity and for decreasing luminescence decay times. Five co-doped samples with three different sensitizers, namely Tm, Tb and Pr were synthesized by solid-state method. Changes in spectral emission behavior and temperature dependent decay time are presented up to 1600 K. The intensity ratio used for temperature measurements was similar for all samples, and decay time decreased for all codopings. Codoping by Tm decreased signal intensity considerably, thus YAG:Dy,Tm is not suitable for high temperature measurements. However, codoping YAG:Dy with Tb and especially Pr resulted in improved luminescent characteristics, and these phosphors are promising for high temperature phosphor thermometry.
Keywords: Thermographic phosphors High temperature thermometry Codoping